Data Mining Extensions (DMX) Reference (SQL Server 2012 Books Online) (Microsoft, 2015)
This book expresses the author’s views and opinions. The information contained in this book is provided without any express, statutory, or implied warranties. Neither the authors, Microsoft Corporation, nor its resellers, or distributors will be held liable for any damages caused or alleged to be caused either directly or indirectly by this book...